Unraveling the influence of salinity on physiological and biochemical parameters in citrus (Citrus spp.) rootstocks - REETIKA,; DALAL, R P S; SOURABH,; RUPAKSHI,; BENIWAL, VIVEK; MEHTA, TANVI; GAUTAM, RAVI (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried out during 2018–19 and 2019–20 at Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to examine the impact of salt stress on physiological parameters of 9 distinct rootstocks of citrus (Citrus spp.) The experimental design followed a completely randomized design (CRD) accompanied with 3 replications, enclosing 45 combinations with 9 citrus rootstocks (Pectinifera, Cleopatra mandarin, Rangpur lime, Alemow, Rough lemon, NRCC-4, Volkamer lemon, CRH-12 and NRCC-3) exposed to 5 NaCl salt stress levels, viz. control (0.07), 2.5, 4.0, 5.5 and 7.0 dS/m. Among the different rootstocks, Rangpur lime exhibited the highest leaf (12.65 mg/g DW) and root (12.42 mg/g DW) total soluble carbohydrates at the 7.0 dS/m salinity level. Additionally, Rangpur lime showcased minimal reduction in chlorophyll stability index (17.2%), leaf and root relative water content (18.7 and 18.9%, respectively), relative stress injury (32.0 and 33.0%, respectively) and leaf and root (Malondialdehyde) MDA content (8.46 and 8.12 µmoles/g DW, respectively) at the same salinity level. Overall, Rangpur lime, Volkamer lemon and CRH-12 demonstrated superior performance by exhibiting relatively higher buildup of total soluble carbohydrates and less drop in CSI, RWC, RSI and MDA content at 7.0 dS/m as compared to control. Conversely, Cleopatra mandarin, Rough lemon and NRCC-3 displayed a relative moderate response, while Pectinifera, Alemow, and NRCC-4 showcased substandard performance, exhibiting contrasting behaviour at 7.0 dS/m as compared to control, particularly concerning physiological parameters at the seedling stage.